PENGARUH PEMBERIAN HORMON ROOTONE-F DAN MEDIA TANAM TERHADAP PERTUMBUHAN STEK PUCUK KAYU PUTIH (Melaleuca cajuputi) - Febriandy, Idfi; Sutriono, Raden; Aji, Irwan Mahakam Lesmono (JURNAL RIMBA LESTARI, 2021)
Melaleuca cajuputi (cajuput) is a plant from the Myrtaceae family that has been widely used, especially by the essential oil industry, which contains the main compound in the form of 1.8 cineol. The research aims to understand the influence of Rootone-F hormone concentration, the effect of planting media, and the interaction between Rootone-F hormone concentration and planting medium on the growth of cajuput cuttings (Melaleuca cajuputi). The design used in this study is the completely randomized design (CRD), with factorials consisting of two factors and three replications, giving the total samples of the study of 48 treatments. The first factor is the hormone (R) consists of 4 levels, namely control 0 ppm (), 100 ppm (), 200 ppm (), and 300 ppm (). The second factor is the growing media (M) consists of 4 levels, namely soil (), soil + cocopeat (), sand + cocopeat (), and cocopeat (). The results show that the use of Rootone-F hormone and planting media have no significant effect on all research parameters (namely: seedling height, seed diameter, number of leaves, root length, and live percentage) of cajuput (Melaleuca cajuputi).